Aortoiliac CT angiography for planning transcutaneous aortic valve implantation: aortic root anatomy and frequency of clinically significant incidental findings - Apfaltrer, Paul; Süselbeck, Tim; Henzler, Thomas; Kriššák, Radko; Schönberg, Stefan; Fink, Christian (American journal of roentgenology, 2012)
OBJECTIVE: The purpose of this article is to assess aortic root and iliofemoral vessel anatomy and the frequency of clinically significant incidental findings on aortoiliac CT angiography (CTA) performed for planning of transcutaneous aortic valve implantation. MATERIALS AND METHODS: Aortoiliac CTA studies of 207 patients scheduled for transcutaneous aortic valve implantation were analyzed. Anatomic dimensions relevant to the interventional procedure, including diameter of the aortic annulus and sinus of Valsalva, distance between aortic annulus and coronary ostia, coronary leaflet length, left ventricular outflow tract diameter, and vessel diameter of iliac arteries, were analyzed. Clinically significant incidental findings were recorded. RESULTS: The mean (± SD) maximum and minimum diameters of the aortic annulus were 29 ± 3.9 mm and 23.5 ± 4.1 mm, respectively. The mean distances between aortic annulus and the ostium of the left and right coronary artery were 13.5 ± 3.2 mm and 14.8 ± 3.9 mm, respectively. The mean maximum and minimum diameters of the left ventricular outflow tract were 27 ± 4 mm and 1.9 ± 4 mm, respectively. The mean diameter of the sinus of Valsalva was 33.4 ± 5.1 mm. The mean diameters of the right and left external iliac artery were 8 ± 1 and 8 ± 2 mm, respectively. Almost half the patients (101/207) had clinically significant incidental findings, including noncalcified pulmonary nodules larger than 8 mm (n = 7), pulmonary embolism (n = 3), or aortic aneurysm (n = 12). CONCLUSION: Aortoiliac CTA provides relevant information on aortic root and iliofemoral vessel anatomy for preinterventional planning. CTA reveals clinically significant incidental findings in a high number of patients considered for transcutaneous aortic valve implantation, which may have a significant impact on patient selection.
Gesehen am 29.06.2018